Myocardial infarction and pulmonary embolism in pancreatic cancer: a case report of two manifestations of Trousseau's syndrome - Oh, Seok; Kim, Ju Han; Sim, Doo Sun; Hong, Young Joon; Ahn, Youngkeun; Jeong, Myung Ho (Frontiers in Cardiovascular Medicine, 2025)
IntroductionThe simultaneous occurrence of acute myocardial infarction (AMI) and venous thromboembolism (VTE) is rare and often associated with underlying malignancies. This study reports a rare case of concurrent AMI and pulmonary thromboembolism in a patient diagnosed with pancreatic cancer.Case presentationA 70-year-old woman presented with acute chest pain and ST-segment elevation myocardial infarction, prompting immediate percutaneous coronary intervention (PCI) with the deployment of a drug-eluting stent. Following PCI, she was treated with optimal medical therapy, including dual antiplatelet therapy. Subsequent investigations revealed pulmonary embolism, deep vein thrombosis, and imaging findings suggestive of pancreatic cancer. Anticoagulation therapy was initiated to manage the VTE. Approximately 1 month after PCI, antithrombotic agents were temporarily discontinued for pancreatic mass biopsy, confirming pancreatic ductal adenocarcinoma. The patient was referred for palliative chemotherapy.DiscussionThis case highlights the clinical manifestation of Trousseau's syndrome, characterized by cancer-associated thromboembolism, and underscores the importance of coordinated antithrombotic management in complex clinical settings.